Polymer composition and use thereof as phase change material

By using polymer compositions with different thermal conductivity fillers and fluoropolymers, the problem of insufficient thermal conductivity and stability of existing phase change materials is solved, and efficient thermal energy storage and solar energy storage are achieved , especially after long-term aging, it still maintains efficient storage capacity.

CN119286091APending Publication Date: 2025-01-10VERSALIS SPA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411340739.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-09-28
Filing Date
2017-09-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing phase change materials have problems with insufficient thermal conductivity and chemical stability in thermal energy storage and solar energy storage applications, especially in the absence of thermal energy storage capacity and mechanical characteristics after long-term aging.

Method used

Using polymer compositions containing ethylene homopolymer or ethylene copolymer, fillers with different thermal conductivity and fluoropolymers, polymer compositions are prepared through an extrusion mechanism to ensure high phase change enthalpy, thermal conductivity and Chemical/physical stability and is used to store latent heat solar energy.

Benefits of technology

High thermal conductivity, excellent thermal energy storage capacity and chemical/physical stability are achieved, ensuring that the polymer composition still has the ability to store solar energy efficiently after aging, and that the fluorine-containing elastomer has no negative impact on thermal properties and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286091A_ABST
    Figure CN119286091A_ABST
Patent Text Reader

Abstract

A polymer composition comprising: (a) from 50% by volume to 99% by volume, preferably from 70% by volume to 95% by volume of at least one ethylene homopolymer or ethylene copolymer; (b) from 1% by volume to 50% by volume, preferably from 5% by volume to 30% by volume, of at least two fillers having different thermal conductivities; (c) from 100 ppm to 4000 ppm, preferably from 200 ppm to 3500 ppm, of at least one fluoropolymer; the sum of (a) + (b) is 100. The polymer composition can be used as a phase change material (PCM), in particular for thermal energy storage (TES), more particularly for storing solar energy.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the patent application with application number 201780060061.9 filed on September 27, 2017 and invention name “Polymer composition and its use as phase change material”. Technical Field

[0002] The present invention relates to polymer compositions and their use as phase change materials (PCMs).

[0003] More particularly, the present invention relates to polymer compositions.

[0004] The polymer composition may be used as phase change material (PCM), in particular for thermal energy storage (TES), more particularly for storing solar energy.

[0005] Therefore, the present invention also relates to the use of the above mentioned polymer composition as phase change material (PCM). Background Art

[0006] Phase change materials (PCMs) are known in the art.

[0007] For example, international patent application WO 2006 / 023860 describes a thermally conductive composition comprising a mixture of a polymer matrix and spherical boron nitride agglomerates as fillers and having an aspect ratio of less than 2, wherein the spherical boron nitride agglomerates are formed from irregular non-spherical particles of boron nitride bound together by a binder and subsequently spray dried. The above-mentioned thermally conductive composition can be used in different forms for applications where thermal management is necessary, including phase change materials (PCMs) in the form of free-standing films or with a thermally conductive carrier, pad or sheet, thermally conductive grease or gel, thermally conductive adhesive or thermally conductive tape.

[0008] US patent application US2011 / 0248208 describes a phase change material (PCM) comprising: (a) from 20% by weight to 80% by weight of a phase change material (PCM), preferably selected from alkyl hydrocarbons (paraffins); (b) from 20% by weight to 80% by weight of one or more polymers selected from the group consisting of: (b1) very-low-density polyethylene (VLDPE), the very-low-density polyethylene having a density less than or equal to 0.910 g / cm2 measured according to standard ASTM 792; 3(b2) ethylene-propylene rubber (EPR), the ethylene-propylene rubber having a density less than or equal to 0.900 g / cm2 measured according to standard ASTM 792 3 density; (b3) styrene-ethylene-butadiene-styrene (SEBS) copolymer; and (b4) styrene-butadiene-styrene (SBS) copolymer; the percentages by weight are based on the total weight of the composition. The above-mentioned phase change material (PCM) is said to be useful in different applications where thermal management is necessary. Although the management of the temperature inside a building is one of the most important applications, the above-mentioned phase change material (PCM) can also be used in automotive applications (e.g., in ceilings, seats and tires of vehicles); or, it can be used in: air filters in air ducts; in transportation; in food packaging (to keep food cold or warm); in pharmaceutical packaging; in fabrics and non-woven fabrics for clothing and sportswear; in footwear; in hand grips (e.g., for tools, sporting goods and vehicles); in bed linens; in carpets; in wood composites; in cables; and in plastic pipes for transporting hot substances including water.

[0009] US patent application US2015 / 0299416 describes a phase change material (PCM) in the form of pellets, the phase change material consisting essentially of: a mixture of paraffin wax, a polymer and optionally a thermal conductivity improver, a nucleating agent, an antioxidant or a mixture thereof; wherein the paraffin wax is at least about 60% of the phase change material (PCM) by weight in the form of pellets; and the polymer is a high density polyethylene (HDPE) having a melt flow index in the range of from 0.1 g / 10 min to 50 g / 10 min. The above-mentioned patent application also describes a process for preparing the phase change material (PCM) in the form of pellets. The above-mentioned phase change material (PCM) in the form of pellets and the continuous pelletizing process described in the above-mentioned patent application are said to be particularly suitable for automation of the process for the preparation of the phase change material (PCM). The phase change material (PCM) in the form of pellets produced with a low production cost pelletizing process can be used in different energy storage applications. Such applications include, for example, energy efficiency products used in the construction of buildings (eg, siding, under-roof insulation, tiles), for clothing, for footwear, for furniture.

[0010] Chinese patent application CN 104893672 describes a composite phase change material (PCM), which comprises: high density polyethylene (HDPE), paraffin wax and inorganic filler. The above-mentioned phase change material (PCM) is said to have good thermal conductivity, high thermal efficiency, good chemical stability and stable phase change temperature. The composite phase change material (PCM) can be used in different applications, such as for interior ceilings, inner walls, heat recovery and similar applications.

[0011] The study of phase change materials (PCMs) remains of great interest since they can be used in different applications.

[0012] The Applicant therefore proposed to solve the problem of finding new polymer compositions that can be used as phase change materials (PCM). Summary of the invention

[0013] The applicant has now found a polymer composition comprising: (a) at least one ethylene homopolymer or ethylene copolymer, (b) at least two fillers with different thermal conductivities, (c) at least one fluoropolymer, which can be advantageously used as a phase change material (PCM), in particular for thermal energy storage (TES), more particularly for storing solar energy. In fact, the polymer composition has excellent thermal properties, such as, for example, high phase change enthalpy and high thermal conductivity. In addition, the polymer composition has high chemical stability / physical stability and high thermal energy storage (TES) capacity after aging. In addition, the polymer composition can advantageously be used to store solar energy in the form of latent heat for its subsequent use. In addition, the presence of the fluoroelastomer does not have a negative impact on other thermal properties, in particular the Vicat softening temperature, or on the mechanical properties (such as elastic modulus) of the polymer composition.

[0014] The object of the present invention is therefore a polymer composition comprising:

[0015] (a) from 50% by volume to 99% by volume, preferably from 70% by volume to 95% by volume, of at least one ethylene homopolymer or ethylene copolymer;

[0016] (b) from 1% by volume to 50% by volume, preferably from 5% by volume to 30% by volume of at least two fillers having different thermal conductivities;

[0017] (c) from 100 ppm to 4000 ppm, preferably from 200 ppm to 3500 ppm, of at least one fluorine-containing polymer;

[0018] The sum of (a)+(b) is 100.

[0019] For the purposes of the present description and the following claims, the definitions of numerical ranges always include the extreme values ​​unless otherwise indicated.

[0020] For the purpose of this specification and the following claims, the term "comprising" also includes the terms "which consists essentially of" or "which consists of. . . . ".

[0021] According to a preferred embodiment of the present invention, the ethylene homopolymer or ethylene copolymer may be, for example, selected from:

[0022] - High-density polyethylene (HDPE);

[0023] - Medium density polyethylene (MDPE);

[0024] - low-density polyethylene (LDPE);

[0025] - linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE), ultra low density polyethylene (ULDPE), which are ethylene and at least one having the formula CH 2 =CH-R copolymers of aliphatic α-olefins, wherein R represents a linear or branched alkyl group containing from 1 to 12 carbon atoms, preferably a linear alkyl group, the aliphatic α-olefin being selected, for example, from: propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene;

[0026] or a mixture thereof.

[0027] According to a particularly preferred embodiment of the present invention, the ethylene homopolymer or ethylene copolymer is a high density polyethylene (HDPE).

[0028] Examples of ethylene homopolymers or ethylene copolymers that can be used in the present invention and that are currently available on the market are the following products: MDPE HT 514 from TotalPetrochemical; DuPont-Dow Elastomers Exxon Chemical

[0029] The ethylene homopolymer or ethylene copolymer mentioned above can be obtained by polymerization techniques known in the art in the presence of a Ziegler-Natta catalyst, or in the presence of a chromium catalyst, or in the presence of a single-site catalyst such as a metallocene catalyst or a semi-metallocene catalyst, or by a free radical process.

[0030] According to a preferred embodiment of the present invention, the (b) at least two fillers having different thermal conductivities may be selected from, for example:

[0031] (b 1 ) a filler having a thermal conductivity less than or equal to 15 W / mK, preferably in the range from 1 W / mK to 10 W / mK;

[0032] (b 2 ) A filler having a thermal conductivity higher than or equal to 50 W / mK, preferably in the range from 80 W / mK to 500 W / mK.

[0033] According to a preferred embodiment of the present invention, the filler (b 1 ) can be selected, for example, from: talc [H 2 Mg 3 (SiO 3 ) 4 ], calcium carbonate (CaCO 3 ), magnesium hydroxide [Mg(OH) 2 ], mica, barium oxide (BaO), boehmite [g-AlO(OH)], diaspore [g-AlO(OH)], gibbsite [Al(OH) 3 ], barium sulfate (BaSO 4 ), wollastonite (CaSiO 3 )、ZrO 2 ), silicon oxide (SiO 2 ), glass fiber, magnesium aluminate [MgO x Al 2 O 3 , where x = from 1.5 to 2.5], dolomite [CaMg(CO 3 ) 2 ], clay, hydrotalcite or mixtures thereof. Talc is preferred.

[0034] According to a preferred embodiment of the present invention, the filler (b 2 ) can be selected from, for example, boron nitride (BN), aluminum nitride (AlN), magnesium silicon nitride (MgSiN 2 ), silicon carbide (SiC), graphite, ceramic-coated graphite, expanded graphite, graphene, carbon fiber, carbon nanotube (CNT), graphitized carbon black or a mixture thereof. Boron nitride (BN) is preferred.

[0035] According to a preferred embodiment of the present invention, the filler (b 1 ) and the filler (b 2) may have an aspect ratio in the range from 5 to 1000, preferably in the range from 10 to 500, the aspect ratio being defined as the ratio between the diameter and the thickness of the filler.

[0036] According to a preferred embodiment of the present invention, the filler (b 1 ) and the filler (b 2 ) may have at least one of the three dimensions in the range from 0.1 μm to 1000 μm, preferably in the range from 3 μm to 500 μm.

[0037] According to a preferred embodiment of the present invention, the polymer composition comprises at least one selected from (b 1 ) and at least one filler selected from (b 2 ) of the filler, selected from (b 1 ) and a filler selected from (b 2 ) of the filler in a ratio ranging from 4:1 to 1:2 by volume, preferably in a ratio ranging from 2:1 to 1:1 by volume.

[0038] According to a preferred embodiment of the present invention, the fluorine-containing polymer (c) may be selected, for example, from fluorine-containing elastomers, mixtures comprising fluorine-containing elastomers and (co)polymers of ethylene, masterbatches comprising fluorine-containing elastomers and (co)polymers of ethylene.

[0039] Examples of fluorine-containing polymers that can be advantageously used for the purposes of the present invention are (co)polymers derived from one or more of the following monomers: vinylidene fluoride, hexafluoropropylene, tetrafluoroethylene.

[0040] Examples of fluoropolymers that can be used in the present invention and are currently available on the market are the following products: DuPont's Freeflow TM GB, Freeflow TM Z100, Freeflow TM Z110, Freeflow TM Z200, Freeflow TM Z210, Freeflow TM Z300, Freeflow TM 10. Freeflow TM RC.

[0041] The polymer composition according to the present invention may optionally contain other additives commonly used in polymer compositions, such as, for example: antioxidants, such as, for example, sterically hindered phenols, phosphites, phosphonites; blowing agents; nucleating agents for blown systems; lubricants; UV stabilizers; dyes; metal deactivators; coupling agents. When present, the additives may be present in the polymer composition according to the present invention in an amount ranging from 0.01 parts by weight to 3 parts by weight, preferably ranging from 0.02 parts by weight to 1 part by weight, relative to 100 parts by weight of (a) + (b).

[0042] The polymer composition according to the present invention can be prepared according to the processes of the prior art.

[0043] For example, the polymer composition according to the invention can be obtained by extrusion by feeding an extruder at the beginning of the extruder (i.e. at the machine mouth) through a separate doser (e.g. a volumetric doser):

[0044] (a) at least one ethylene homopolymer or ethylene copolymer;

[0045] (b) at least two fillers having different thermal conductivities;

[0046] (c) at least one fluorine-containing polymer;

[0047] and optionally other additives as described above.

[0048] The extruder may be selected, for example, from a co-rotating or counter-rotating twin-screw extruder or a single screw extruder. Preferably, the extrusion may be carried out at a temperature in the range of from 150° C. to 230° C., at a pressure in the range of from 10 bar to 50 bar, and for an amount of time sufficient to obtain a uniform distribution of the compounds contained in the polymer composition in the polymer, typically for a time in the range of from 0.5 minute to 5 minutes, the time being understood as the residence time of the polymer composition in the extruder. At the end of the extrusion, the polymer composition obtained may be pelletized and then formed and shaped by techniques known in the art, such as compression molding.

[0049] A further object of the present invention is the use of said polymer composition as phase change material (PCM), in particular for thermal energy storage (TES), more particularly for storing solar energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 Phase change enthalpies of polymer compositions according to embodiments of the present invention are shown. DETAILED DESCRIPTION

[0051] For the purpose of better understanding the invention and putting it into practical use, the following are certain illustrative and non-limiting examples of the invention.

[0052] Example 1 (Comparative)

[0053] 100% by volume of high-density polyethylene (HDPE) (Versalis spa MR 80U) was loaded into a co-rotating twin-screw extruder (D=30 mm; L / D=28) equipped with a die plate with cylindrical holes having a diameter of 3 mm, a length of 20 mm and a flow rate of 4.50 kg / h per individual extrusion hole. Operating at a constant temperature profile of 200°C, a constant pressure profile of 26 bar, a flow rate of 4.50 kg / h per individual hole and a screw rotation speed of 100 rpm, all were extruded. The material extruded in the form of "spaghetti" was cooled in a water bath, dried in air and granulated using a chopper. Parts of the granules obtained were compression molded at 240°C, 100 bar for 5 minutes to obtain plaques with dimensions of 20×20×2 cm, which were subjected to thermal conductivity analysis: the data obtained are reported in Table 1.

[0054] The thermal conductivity analysis was performed according to the method described in Gustafsson SE et al., "Journal of Physics D: Applied Physics" (1979), Vol. 12, No. 9, pp. 1411-1421, regarding the equipment used; Gustafsson SE, "Journal of Applied Physics" (1982), Vol. 53, No. 9, pp. 6064-6068, regarding the thermal conductivity calculations.

[0055] Portions of the granules obtained were compression molded at 200°C, 100 bar for 5 minutes, obtaining specimens with dimensions 15x40x4 mm subjected to Vicat softening temperature measurements (1 kg-50°C / h) equal to 126°C operating according to standard ISO 306:2004 method A50.

[0056] Example 2 (Comparative)

[0057] 80% by volume of high density polyethylene (HDPE) (Versalis spa MR 80U), 10% by volume of talc (aspect ratio = 15; maximum size: 35 μm) (Imerys-FGRM) and 10% by volume of boron nitride (aspect ratio = 30; maximum size: 20 μm) (Boron Nitride Cooling Filler Platelets Grade 15 / 400) were loaded into a co-rotating twin-screw extruder (D = 30 mm; L / D = 28) equipped with a die plate with cylindrical holes having a diameter of 3 mm, a length of 20 mm and a flow rate of 1.50 kg / h per individual extrusion hole. All were extruded operating at a constant temperature profile of 200° C., a constant pressure profile of 26 bar, a flow rate of 1.50 kg / h per individual hole and a screw rotation speed of 100 rpm. The material extruded in the form of "spaghetti" was cooled in a water bath, dried in air and granulated using a chopper. Portions of the granules obtained were compression moulded at 240° C., 100 bar, for 5 minutes, obtaining plaques having dimensions of 20×20×2 cm which were subjected to thermal conductivity analysis operated as described in Example 1 : the data obtained are reported in Table 1 .

[0058] Portions of the granules obtained were compression molded at 200°C, 100 bar for 5 minutes, obtaining specimens with dimensions 15x40x4 mm subjected to Vicat softening temperature measurements (1 kg-50°C / h) equal to 126°C operating according to standard ISO 306:2004 method A50.

[0059] During extrusion, after operating the extruder for about 3 hours, the formation of die buildup was observed on the die plate. It should be noted that the formation of die buildup may cause the formation of irregularities on the surface of the extruded material, which may lead to die cracking and thus require stopping the extruder in order to clean the die plate.

[0060] Embodiment 3 (present invention)

[0061] 80% by volume of high density polyethylene (HDPE) (Versalis spa MR 80U), 10% by volume of talc (aspect ratio = 15; maximum dimension: 35 μm) (Imerys-FGRM) and 10% by volume of boron nitride (aspect ratio = 30; maximum dimension: 20 μm) (boron nitride cooling filler flake grade 15 / 400) and 500 ppm of fluoropolymer (DuPont's Freeflow TMGB) are loaded into a co-rotating twin-screw extruder (D=30 mm; L / D=28) equipped with a die plate with cylindrical holes having a diameter of 3 mm, a length of 20 mm and a flow rate of 1.70 kg / h per individual extrusion hole. All are extruded operating at a constant temperature profile of 200°C, a constant pressure profile at 26 bar, a flow rate of 1.70 kg / h per individual hole and a screw rotation speed of 100 rpm. The material extruded in the form of "spaghetti" is cooled in a water bath, dried in air and granulated using a chopper. Part of the granules obtained is compression molded at 240°C, 100 bar for 5 minutes to obtain plaques with dimensions of 20×20×2 cm, which are subjected to a thermal conductivity analysis operated as described in Example 1: the data obtained are reported in Table 1.

[0062] A portion of the granules obtained was compression molded at 200° C., 100 bar, for 5 minutes, obtaining a sample with dimensions 15×40×4 mm, which was subjected to Vicat softening temperature measurement (1 kg-50° C. / h) equal to 126° C., operating according to standard ISO 306:2004 method A50

[0063] During extrusion, no formation of die buildup was observed on the die plate, even after operating the extruder for 5 hours.

[0064] For the purpose of determining the enthalpy of the phase change by means of a Perkin Elmer Pyris differential scanning calorimeter, a portion of the particles obtained was also subjected to DSC (Differential Scanning Calorimetry). For this purpose, 10 mg of the particles were analyzed in an inert nitrogen atmosphere at a scanning rate of 20° C. / min in cooling and 5° C. / min in heating: the results obtained are reported in Figure 1 In, from Figure 1 It can be inferred that the polymer composition obtained as described above has a phase change enthalpy of 151.6 J / g when melted and a phase change enthalpy of 170.7 J / g when crystallized.

[0065] Embodiment 4 (present invention)

[0066] 80% by volume of high density polyethylene (HDPE) (Versalis spa MR 80U), 10% by volume of talc (aspect ratio = 15; maximum dimension: 35 μm) (Imerys-FGRM) and 10% by volume of boron nitride (aspect ratio = 30; maximum dimension: 20 μm) (boron nitride cooling filler platelet grade 15 / 400) and 3000 ppm of fluoropolymer (DuPont's Freeflow TMGB) are loaded into a co-rotating twin-screw extruder (D=30 mm; L / D=28) equipped with a die plate with cylindrical holes having a diameter of 3 mm, a length of 20 mm and a flow rate of 2.15 kg / h per individual extrusion hole. All are extruded operating at a constant temperature profile of 200°C, a constant pressure profile at 26 bar, a flow rate of 2.15 kg / h per individual hole and a screw rotation speed of 100 rpm. The material extruded in the form of "spaghetti" is cooled in a water bath, dried in air and granulated using a chopper. Part of the granules obtained is compression molded at 240°C, 100 bar for 5 minutes to obtain plaques with dimensions of 20×20×2 cm, which are subjected to a thermal conductivity analysis operated as described in Example 1: the data obtained are reported in Table 1.

[0067] Portions of the granules obtained were compression molded at 200°C, 100 bar for 5 minutes, obtaining specimens with dimensions 15x40x4 mm subjected to Vicat softening temperature measurements (1 kg-50°C / h) equal to 126°C operating according to standard ISO 306:2004 method A50.

[0068] During extrusion, no formation of die buildup was observed on the die plate, even after operating the extruder for about 5 hours.

[0069] Table 1

[0070]

[0071] From the data reported in Table 1, it can be deduced that the presence of fluoroelastomer [Example 3 (inventive) and Example 4 (inventive)] does not affect the thermal conductivity which remains constant relative to Example 2 (comparative), however, Example 2 (comparative) shows a lower extrusion flow per individual hole (equal to 1.50 kg / h) relative to both Example 3 (inventive) (equal to 1.70 kg / h) and Example 4 (inventive) (equal to 2.15 kg / h). Furthermore, it can be deduced that the presence of fluoroelastomer [Example 3 (inventive) and Example 4 (inventive)] allows preventing mold buildup on the die plate even after 5 hours of operation of the extruder.

Claims

1. A phase change material suitable for thermal energy storage comprising a polymer composition, the polymer composition comprising: (a) from 80% by volume to 99% by volume of at least one ethylene homopolymer or ethylene copolymer; (b) from 1% by volume to 20% by volume of at least two fillers having different thermal conductivities: (b1) a filler having a thermal conductivity less than or equal to 15 W / mK; (b2) a filler having a thermal conductivity greater than or equal to 50 W / mK; From 100 ppm to 4000 ppm of at least one fluoropolymer; wherein the at least one ethylene homopolymer or ethylene copolymer and the at least one fluoropolymer are the only (co)polymers in the composition and the sum of (a) + (b) is 100.

2. The phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the ethylene homopolymer or ethylene copolymer is selected from: - High-density polyethylene (HDPE); - Medium density polyethylene (MDPE); - low density polyethylene (LDPE); - linear low-density polyethylene (LLDPE), very low-density polyethylene (VLDPE), ultra-low-density polyethylene (ULDPE), which are copolymers of ethylene and at least one aliphatic α-olefin of formula CH2=CH-R, in which R represents a linear or branched alkyl group containing from 1 to 12 carbon atoms, the aliphatic α-olefin being chosen from: propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene; or a mixture thereof.

3. The phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the filler (b1) is selected from the group consisting of talc [H2Mg3(SiO3)4], calcium carbonate (CaCO3), magnesium hydroxide [Mg(OH)2], mica, barium oxide (BaO), boehmite [g-AlO(OH)], diaspore [g-AlO(OH)], gibbsite [Al(OH)3], barium sulfate (BaSO4), wollastonite (CaSiO3), zirconium oxide (ZrO2), silicon oxide (SiO2), glass fiber, magnesium aluminate [MgO x Al2O3, wherein x = from 1.5 to 2.5], dolomite [CaMg(CO3)2], clay, hydrotalcite or mixtures thereof.

4. A phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the filler (b2) is selected from: boron nitride (BN), aluminum nitride (AlN), magnesium silicon nitride (MgSiN2), silicon carbide (SiC), graphite, ceramic-coated graphite, expanded graphite, graphene, carbon fiber, carbon nanotubes (CNT), graphitized carbon black or a mixture thereof.

5. The phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the filler (b1) and the filler (b2) have: - an aspect ratio, the aspect ratio being defined as the ratio between the diameter and the thickness of the filler, the ratio being in the range from 5 to 1000; and / or - At least one of the three dimensions in the range from 0.1 μm to 1000 μm. 6 . The polymer composition according to claim 1 , wherein the at least one filler (b1) and the at least one filler (b2) are present in a ratio ranging from 4:1 to 1:2 by volume.

7. A phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the fluorine-containing polymer (c) is selected from a fluorine-containing elastomer, a mixture comprising a fluorine-containing elastomer and an ethylene (co)polymer, and a masterbatch comprising a fluorine-containing elastomer and an ethylene (co)polymer.

8. The phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, comprising from 200 ppm to 3500 ppm of the at least one fluorine-containing polymer.

9. A phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the filler (b1) has a thermal conductivity in the range of from 1 W / mK to 10 W / mK, and the filler (b2) has a thermal conductivity in the range of from 80 W / mK to 500 W / mK.

10. The phase change material suitable for thermal energy storage comprising a polymer composition according to claim 5, wherein the filler (b1) and the filler (b2) have: said aspect ratio in the range from 10 to 500; and / or at least one of the three dimensions in the range from 3 μm to 500 μm.

11. The phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the at least one filler (b1) and the at least one filler (b2) are present in a ratio ranging from 2:1 to 1:1 by volume.

12. The phase change material suitable for thermal energy storage comprising a polymer composition according to claim 1, wherein the at least one fluorine-containing polymer does not reduce the thermal conductivity of the polymer composition.

Citation Information

Patent Citations

  • Phase change material (PCM) compositions for thermal management

    US20110248208A1

  • Low cost process for manufacture of form-stable phase change material

    US20150299416A1

  • Thermally conductive composition and method for preparing the same

    WO2006023860A2